Healthcare facility factors associated with health-seeking behavior among secondary school students in the Dodoma region: an analytical cross-sectional study - Karim Faragha Athumani; Joanes Faustine Mboineki (Frontiers in Public Health)
BackgroundHealth-seeking behavior (HSB) is an important aspect of population health and is closely linked to a nation’s economic development. Its importance is reflected in the Sustainable Development Goal 3. Although previous studies in Tanzania have examined health-seeking behavior, the majority of them have focused on the behavior of seeking medical attention after becoming sick. The present study assessed healthcare facility factors associated with health-seeking behavior among secondary school students in the Dodoma region.MethodologyThis was a cross-sectional analytical study that included 311 adolescent secondary school students. The data were collected through a validated questionnaire and were analyzed using descriptive statistics and chi-squared test values (χ2).ResultsAmong the 311 study respondents, 62 (19.9%) were found to exhibit health-seeking behavior. Healthcare facility factors associated with adolescents’ health-seeking behavior included healthcare service costs (χ2 = 12.415, p = 0.015) and long queues (χ2 = 10.077, p = 0.039).ConclusionThe health-seeking behavior among adolescents was not satisfactory and is influenced by factors such as service costs, long queues, and their socio-demographic characteristics (age, sex, and education). Improving adolescents’ health-seeking behavior requires reducing hospital waiting times and queues. To address cost barriers to health-seeking behavior, initiatives should be implemented to ensure that each secondary school student has health insurance. Interventions need to consider adolescents’ age, sex, and education to improve their health-seeking behavior. For instance, priorities should be directed toward very young adolescents and those with lower levels of education.